Spinal Tuberculosis: Current Management Approach - Onuminya, John E.; Morgan, Eghosa; Shobode, Mutaleeb Ayodele (Nigerian Journal of Orthopaedics and Trauma, 2019)
Broad narrative review. To review and summarise the current literature on the management of tuberculosis (TB) spine. A thorough review of literature was performed on the epidemiology, aetiology, pathophysiology, pathology, clinical features and management of TB spine. Spinal TB accounts for half of skeletal TB and remains a common cause of public health concern in the developing world. The thoracic spine segment is the most affected. Patient commonly present with back pain and gibbus. The diagnosis involves demonstrating Mycobacterium tuberculosis on microscopy or culture as well as characteristic histology findings. Magnetic resonance imaging is the gold standard imaging modality. Medical therapy with anti‑TB agents is the mainstay of treatment. Surgery is supplementary and indicated in selected cases. Spinal TB carries a good prognosis when detected and treated early. Delays can be associated with the development of complications including difficult‑to‑manage deformities. Multi‑drug anti TB chemotherapy remains the bedrock of treatment. Surgery is supplementary and when indicated, takes the form of abscess drainage, debridement and fusion with or without instrumentation.